Pengaruh blended learning flex model berbantuan media video terhadap hasil belajar IPA materi ekosistem - Setyo Ariawan; Agrissto Bintang Aji Pradana; Tawil Tawil (Borobudur Educational Review, 2021)
This study aims to determine the effect of Blanded Learning Flex Model assisted by video on science learning outcomes of the fifth grade ecosystem material at SDN Kuwaluhan, Secang, Magelang. The research design used pre-experimental design with One Group Pretest Postest Design research model. This research was conducted in class V SDN Kuwaluhan, Secang District, Magelang Regency. The total sample of the study was taken from the population with a total sample size of 28 students using a total sampling technique. The method used in data collection in this study is the test method. The validity test carried out in this study is construct validity and empirical validity. The normality test in this study obtained a significance value of 0.05 ≥ 0.05 where the data was declared normal. The reliability test used Cronbach's alpha which resulted in a reliability index of 0.941. The results of the hypothesis test are shown by the Paired Samples T Test data on the learning outcomes of science learning with t value> t table, namely 12,755> 1,701 with a sig value. (2 tailed) 0.000 <0.05, which indicates that there is an effect of the Blanded Learning Flex Model learning assisted by video on the science learning outcomes of the ecosystem material. The results of this study prove that there is an effect of Learning Blanded.